Amplification of RAD54B promotes progression of hepatocellular carcinoma via activating the Wnt/β-catenin signaling - Senwen Feng; Junhao Liu; Li Hailiang; Jianfan Wen; Yujun Zhao; Xiaofeng Li; Guankun Lu; Peng Gao; Xiancheng Zeng (Translational Oncology, 2021)
Liver cancer was reported to be the sixth most frequently diagnosed cancer, and hepatocellular carcinoma (HCC) accounts for 75%-85% of primary liver cancer. Nevertheless, the concrete molecular mechanisms of HCC progression remain obscure, which is essential to elucidate. The expression profile of RAD54B in HCC was measured using qPCR and western blotting. Moreover, the levels of RAD54B in paraffin-embedded samples were evaluated using immunohistochemistry (IHC). The effect of RAD54B on HCC progression was testified by in vitro experiments, and in vivo orthotopic xenograft tumor experiments. The mechanisms of RAD54B promoting HCC progression were investigated through molecular and function experiments. Herein, RAD54B are dramatically upregulated in HCC tissues and cell lines both on mRNA and protein levels, and RAD54B can servers as an independent prognostic parameter of 5-year overall survival and 5-year disease-free survival for patients with HCC. Moreover, up-regulation of RAD54B dramatically increases the capacity for in vitro cell viability and motility, and in vivo intrahepatic metastasis of HCC cells. Mechanistically, RAD54B promotes the HCC progression through modulating the wnt/β-catenin signaling. Notably, blocking the wnt/β-catenin signaling axis can counteract the activating effects of RAD54B on motility of HCC cells. Besides, further analysis illustrates that DNA amplification is one of the mechanisms leading to mRNA overexpression of RAD54B in HCC. Our findings indicate that RAD54B might be a promising potential prognostic marker and a candidate therapeutic target to therapy HCC.